Human macrophage cathepsin β‐mediated C‐terminal cleavage of apolipoprotein α‐I at Ser228 severely impairs antiatherogenic capacity. Issue 12 (14th September 2016) - Dinnes, Donna Lee M.; White, Melanie Y.; Kockx, Maaike; Traini, Mathew; Hsieh, Victar; Kim, Mi‐Jurng; Hou, Liming; Jessup, Wendy; Rye, Kerry‐Anne; Thaysen‐Andersen, Morten; Cordwell, Stuart J.; Kritharides, Leonard
ABSTRACT: Apolipoprotein α‐I (apoA‐I) is themajor component of HDLandcentral to the ability of HDLto stimulate ATP‐binding cassette transporter A1 (ABCA1)‐dependent, antiatherogenic export of cholesterol from macrophage foam cells, a key player in the pathology of atherosclerosis. Cell‐mediated modifications of apoA‐I, such as chlorination, nitration, oxidation, and proteolysis, can impair its antiatherogenic function, although it is unknown whether macrophages themselves contribute to such modifications. To investigate this, human monocyte‐derived macrophages (HMDMs) were incubated with human apoA‐I under conditions used to induce cholesterol export. Two‐dimensional gel electrophoresis and Western blot analysis identified that apoA‐I is cleaved ( 20–80%) by HMDMs in a time‐dependent manner, generating apoA‐I of lower MW and isoelectric point. Mass spectrometry analysis identified a novel C‐terminal cleavage site of apoA‐I between Ser 228 ‐Phe 229 . Recombinant apoA‐I truncated at Ser 228 demonstrated profound loss of capacity to solubilize lipid and to promoteABCA1‐dependent cholesterol efflux. Protease inhibitors, small interfering RNA knockdown in HMDMs, mass spectrometry analysis, and cathepsin B activity assays identified secreted cathepsin B as responsible for apoA‐I cleavage at Ser 228 . Importantly, C‐terminal cleavage of apoA‐I was also detected in human carotid plaque. Cleavage at Ser 228 is a novel, functionally important post‐translationalmodification of apoA‐Imediated byHMDMsthat limits the antiatherogenic properties of apoA‐I.—Dinnes, D. L.M., White, M. Y., Kockx, M., Traini, M., Hsieh, V., Kim, M.‐J., Hou, L., Jessup, W., Rye, K.‐A., Thaysen‐Andersen, M., Cordwell, S. J., Kritharides, L. Human macrophage cathepsin B‐mediated C‐terminal cleavage of apolipoprotein A‐I at Ser 228 severely impairs antiatherogenic capacity. FASEB J. 30, 4239–4255 (2016). www.fasebj.org